2011
DOI: 10.5586/asbp.2010.015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of drought on proline accumulation and peroxidases activity in leaves of Festuca rubra L. and Lolium perenne L.

Abstract: The effect of soil drought on leaf water content, proline content, and the activity of guaiacol (GuPX) and ascorbate (APX) peroxidases as well as the level of lipid peroxidation were investigated in leaves of drought resistant red fescue (Festuca rubra) and drought sensitive perennial ryegrass (Lolium perenne). Plants were grown under glasshouse conditions in soil pot culture. 26 day-old grasses were exposed to drought by withholding irrigation for 18 days. Water content in leaves of perennial ryegrass decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
3
17
0
1
Order By: Relevance
“…YS-1L and YS-2L had much lower MDA contents during the water stress period than ZY1, MXLK, ALLT and 87341. A similar trend was observed by many researchers (Fazeli et al 2007;Lu et al 2008;Moussa & Abdel-Aziz 2008;Bandurska & Jozwiak 2010). All of them showed that YS-1Li is the most drought tolerant genotype of wheat species investigated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…YS-1L and YS-2L had much lower MDA contents during the water stress period than ZY1, MXLK, ALLT and 87341. A similar trend was observed by many researchers (Fazeli et al 2007;Lu et al 2008;Moussa & Abdel-Aziz 2008;Bandurska & Jozwiak 2010). All of them showed that YS-1Li is the most drought tolerant genotype of wheat species investigated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, individual varieties of Lolium were characterized by variable levels of proline accumulation in the four investigated periods, without a clear trend (Table ). The accumulation of free proline under drought conditions in forage grasses was confirmed by many authors (Bokhari and Trent , Bandurska and Jóźwiak , Man et al. ).…”
Section: Discussionsupporting
confidence: 59%
“…Drought turned out to be the most detrimental abiotic stress that limited crop yield by as much as 30-80% [45]. Scientists and breeders are gradually improving crop plant genotypes in terms of drought tolerance using both traditional selection methods and genetic engineering [26,34]. However, tolerance to drought stress is a complex feature, and finding suitable phenotypes requires time-consuming exposure of plants to simultaneously or sequentially occurring stress factors in natural conditions.…”
Section: Discussionmentioning
confidence: 99%